1995
DOI: 10.1002/1520-6629(199501)23:1<74::aid-jcop2290230107>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Comfort and conflict in the relationships of pregnant, minority adolescents: Social support as a moderator of social strain

Abstract: Although there is growing recognition that social strain can be a source of considerable distress, few studies to date have examined the ways in which social support may moderate social strain. In this study, social strain was conceived of as a stressor in its own right, whose adverse effects were expected to be alleviated by social support. Participants were 157 pregnant, minority teenagers, all of whom were attending an alternative school for pregnant students. Life events and social strain were positively r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 27 publications
1
28
2
Order By: Relevance
“…In either case, the literature holds that both are essential to the mental health effects of social support. Indeed, findings show that both positive social support and lack of social undermining effect individuals' mental health by buffering the impact of stressful life events (Lakey, Tardiff, & Drew, 1994; Rhodes & Woods, 1995). In light of this, we hypothesized the following:…”
Section: Social Support In the Lives Of Sexual Minority Youthmentioning
confidence: 99%
“…In either case, the literature holds that both are essential to the mental health effects of social support. Indeed, findings show that both positive social support and lack of social undermining effect individuals' mental health by buffering the impact of stressful life events (Lakey, Tardiff, & Drew, 1994; Rhodes & Woods, 1995). In light of this, we hypothesized the following:…”
Section: Social Support In the Lives Of Sexual Minority Youthmentioning
confidence: 99%
“…It is estimated that 3–5% of women meet criteria for major depression during pregnancy, with an approximately equivalent number experiencing subclinical depressive symptoms (Gaynes et al, 2005). Women who lack social support or experience greater social conflict are likely to experience more depressive symptoms during pregnancy (Rhodes and Woods, 1995). Moreover, rates of both depression (Seguin et al, 1995) and preterm delivery (Goldenberg et al, 2008) are substantially higher among women from lower versus higher socioeconomic backgrounds.…”
mentioning
confidence: 99%
“…Ingersoll‐Dayton and colleagues (1997) found that negative exchanges were associated with negative affect, particularly among those experiencing more stressful life events. In addition, Rhodes and Woods (1995), using a sample of adolescent mothers, reported that social strain was positively related to depression. Despite these robust findings, few studies have simultaneously assessed both social support and social strain when attempting to understand the impact of social networks on psychological well‐being.…”
mentioning
confidence: 99%